Inhibition of chondroitin sulphate-degrading enzyme Chondroitinase ABC by dextran sulphate - Sagar Dalal; Rachana Pathak; Edward X. S. Moh; Nicolle H. Packer (Glycoconjugate Journal, 2025)
Chondroitin sulphate (CS) is a sulphated glycosaminoglycan (GAG) polysaccharide found on proteoglycans (CSPGs) in extracellular and pericellular matrices. Chondroitinase ABC (CSase ABC) derived from Proteus vulgaris is an enzyme that has gained attention for the capacity to cleave chondroitin sulphate (CS) glycosaminoglycans (GAG) from various proteoglycans such as Aggrecan, Neurocan, Decorin etc. The substrate specificity of CSase ABC is well-known for targeting various structural motifs of CS chains and has gained popularity in the field of neuro-regeneration by selective degradation of CS GAG chains. Within this context, our investigation into the biochemistry of CSase ABC led us to a previously unreported inhibition of CSase ABC activity by Dextran Sulphate (DexS). To understand the inhibitory effects of DexS, we compared its inhibition of CSase ABC to that of other polysaccharides such as Heparan Sulphate, Heparin, Colominic Acid, Fucoidan, and Dextran. This analysis identified key structural factors such as monosaccharide composition and linkage, sulphation degree and overall charge as influencing CSase ABC inhibition. Remarkably, DexS emerged as a unique inhibitor of CSase ABC, with distinctive inhibitory effects that correlate with its chain length. DexS has been used to reliably induce ulcerative colitis in mice, effectively mimicking inflammatory bowel diseases in humans, and has been previously shown to inhibit both RNA polymerase and reverse transcriptase. Our investigation emphasizes the interplay between the properties of DexS and CSase ABC, providing significant insights into the utilization of polysaccharide-based inhibitors for modulating enzyme activity.